Emotional and Behavioral Changes and Related Factors of Firstborn School-Aged Compared to Same Age Only Children - Sheng, Lulu; Yang, Bo; Story, Mary; Wu, Wenyi; Xi, Xuan; Zhou, Yuanke; Wen, Yi; Wang, Hong; Liu, Qin (Frontiers in Public Health, 2022)
Objective To compare the emotional and behavioral characteristics of firstborn children during the pregnancy of a second child and only children of school-age in urban districts of Chongqing, China, and to explore the influencing factors of emotional and behavioral problems. Methods We recruited mothers of firstborn children and only children from two hospitals and one primary school using purposive sampling. Questionnaires and the Parental Child Behavior Checklist (CBCL) were used to collect basic information, family socioeconomic status, family atmosphere and emotional and behavioral characteristics of their children in the survey. Results The sample consisted of 1,155 children, including 477 firstborn children and 678 only children. The average scores of internalizing (4.47), externalizing (6.05), total problems (22.04), and six emotional and behavioral of firstborn children were significantly lower than those of only children (p < 0.05). When adjusted for children's demographic, socioeconomic and family relationship covariates, the scores of firstborn children internalizing problems (β = −1.423, p = 0.000), externalizing problems (β = −0.661, p = 0.048), and total problems (β = −4.387, p = 0.000) were also significantly lower than those of only children. All children with more difficult parenting and development temperament, greater family economic pressure, poorer relationships between mother and child, less harmonious family atmosphere and father's permissive parenting style had more internalizing problems, externalizing problems and total problems (p < 0.05). Boys had more externalizing problems (β = 1.939, 95% CI = 1.380–2.497) and total problems (β = 4.908, 95% CI = 3.045–6.772) than girls. Conclusion Firstborn children had fewer emotional and behavioral problems than their counterparts who were only children. This research helps to understand the social impact of the implementation of the two-child policy in multiple dimensions.